PELESTARIAN HUTAN MANGROVE DI TELUK BENOA BALI: TINJAUAN DARI ASPEK EKONOMI LINGKUNGAN - WIRADHARMA, I GUSTI BAGUS MADE; ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Indonesia is known as the archipelago country, in which the islands are connected by the sea. As the archipelago country Indonesia has a lot of good nature resources both in land including coastal area and in the sea, so that Indonesia is also known as maritime country. However, because the society does not have enough knowledge in managing them many of the nature resources become damaged. This is also caused by the people in their own activities for earning a living do not take care of the sustainability of the living and non living resources and their ecosystem. The mountaineering area of Mangrove in Teluk Benoa Bali having the status as the forest preserve or protected forest named TAHURA Ngurah Rai, cannot avoid the pressures caused by the changes and the conversion. The mangrove forest tends to give benefits for little society, but those societies actually decrease its support and its capacity such as; making fishpond, garbage disposal, housing, reclamation, fuel pipeline, etc. This situation, of course, decreases the better function and advantages of the mangrove forest in Teluk Benoa. It needs an analysis to determine the social benefits and economic value of the forest mangrove itself so that if it is conserved with the conservation scenario, which is in the future can be used by the policy maker for determining the management option, it will be known if the land conversion of the mangrove can be done or allowed to happen continuously? Then through the analysis of economic for environment by using investment, that is Net Present Value/NPV, B-C Ratio (also by considering the changes of condition of sensitivity analysis) and total economic value especially for the purpose of preservation with the conservation scenario it is concluded that the preservation of the mangrove forest give social benefit of Rp. 94.288.557,59 per hectare a year and the increase investment cost and routine is 10% and the decrease of the price is 5% giving social benefit of Rp. 93.003.794,32 and Rp. 88.931.748,08. In normal condition the increase investment cost and routine is 10% and the decrease of the price is 5% giving NPV in a row; Rp. 831.903.896, 27; Rp. 818.526.222, 18 and Rp. 783.619.864,41 per hectare per year. The same condition like above gives B-C Ratio in a row; 7,22; 6,56 and 6,86. This shows that in any kind of condition the preservation of the mangrove forest in Teluk Benoa Bali is suitable to do. The total value of the economic also shows the yearly asset value of the society in the form of nature resources/ mangrove forest of this area (1,373,5 hectare) is in the three conditions; Rp.129.505.333.853,32; Rp.127.740.711.499,67 and Rp..147.755.983,83 a year. According to those conclusion it can suggested that the function of mangrove forest in Teluk Benoa Bali can be managed accordingly so that the environmental function can run well. Besides, economic value can be used as the reference for coastal management to sustainability.
Keywords: Preservation, Conservation, Social Benefit, Total Economic Value, Sustainability